2020
DOI: 10.1186/s12890-020-1131-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for ARDS: clinical, physiological and atypical immunodeficiency

Abstract: Background: Risk factors affecting the prognosis of acute respiratory distress syndrome (ARDS) in adults were investigated. The aim was to identify new predictors for ARDS patient prognosis, including those with clinical, pathophysiological, and atypical immunodeficiency. Methods: ARDS patients were retrospectively included. The patients were grouped and analysed according to different oxygenation index grades and prognosis, and factors influencing prognosis and survival were examined. Adolescent patients, pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Univariate analysis showed that patients with worse measures of disease severity including SOFA, P/F ratio, or requirement of IMV support, and days on MV had significantly worse mortality, which are known prognostic factors for worse outcomes in ARDS. 37 38 Finally a low ADAMTS13 level was associated with higher mortality in our study. Previous investigations have implicated ADAMTS13 levels as a marker for elevated risk of thrombosis and mortality.…”
Section: Discussionsupporting
confidence: 56%
“…Univariate analysis showed that patients with worse measures of disease severity including SOFA, P/F ratio, or requirement of IMV support, and days on MV had significantly worse mortality, which are known prognostic factors for worse outcomes in ARDS. 37 38 Finally a low ADAMTS13 level was associated with higher mortality in our study. Previous investigations have implicated ADAMTS13 levels as a marker for elevated risk of thrombosis and mortality.…”
Section: Discussionsupporting
confidence: 56%
“…A large number of Fig. 1 Receiver operating characteristic curve analysis for NLR for prognostic value for PSI studies have shown that higher NLR might be an independent predictor of clinical outcome in a variety of diseases, including malignant tumors, acute respiratory distress syndrome, fibrotic liver disease and cardiovascular diseases [29][30][31][32]. At present, it has been paid more attention in the research of neurovascular diseases [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after hyperoxia, lungs exhibited pulmonary edema, alveolar infiltration, a greater number of macrophages, and a lower number of lymphocytes compared with the negative control group. Song et al (Song et al, 2020) also indicated that as ARDS severity increases, lymphocyte counts decrease. However, the groups posttreated with 25 or 50 μg/g aspirin exhibited less pulmonary edema and alveolar infiltration, a lower number of macrophages, and a greater number of lymphocytes than the group exposed to hyperoxia alone.…”
Section: Discussionmentioning
confidence: 98%